EVALUASI KINERJA DINAS PERHUBUNGAN DALAM PELAKSANAAN PELAYANAN PARKIR DI KOTA PEKANBARU - Putri, Dzaskhia Delvani; Sadad, Abdul (Yayasan Amanah Nur Aman, 2025)
Parking is an activity of placing a vehicle in a certain place for a temporary period, either in a specifically designated area or in a public space, in accordance with applicable regulations. The effective organization of parking services is the responsibility of the regional government through the Parking Unit of the Pekanbaru City Transportation Department. This research aims to evaluate the performance of the Parking Unit of the Transportation Department in organizing parking services, which includes identifying the factors that influence the performance of parking service organization. The research method used in this study is qualitative with a descriptive case study approach. Data and research sources are from the results of interviews, observations, and documentation. The research results show that the performance of the Parking Unit of the Transportation Department in organizing parking services in Pekanbaru City still needs to be improved. The factors that influence this performance include limitations in human resources and budget, lack of supervision, and low public awareness regarding orderly parking. Efforts that can be made are by increasing the capacity of human resources, increasing the budget, maximizing supervision, and increasing effective socialization to the community to improve the performance of parking service organizations in Pekanbaru City.